Analysis of the Effect of Corruption and Shadow Economy on the Economy and Sustainable Development of Developing Countries in the Asean Region Developing Countries in the ASEAN Region - Ridho Irawan; Sirojuzilam Hasyim; Raina Linda Sari (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research aims to analyze the impact of corruption and shadow economy on the economy and sustainable development in developing countries in the ASEAN region. Corruption and shadow economy are two interrelated phenomena that have serious implications for governance, resource allocation efficiency, and the achievement of long-term development goals. This research uses a quantitative approach with the Panel Autoregressive Distributed Lag (Panel ARDL) method to identify short-term and long-term effects among variables. The variables used include corruption perception index (CPI), size of the shadow economy (SE), Gross Domestic Product per capita (GDP per capita), and Sustainable Development Index (SDG Index). The data used are secondary data obtained from various official institutions such as the World Bank, International Monetary Fund (IMF), and the Sustainable Development Report (SDR). The research results show that in the short term, neither corruption nor the shadow economy has a significant effect on GDP per capita or the SDG Index. However, in the long term, the shadow economy has a negative and significant effect on GDP per capita and the SDG Index. Meanwhile, corruption (CPI) also has a negative and significant effect on GDP per capita, but shows a positive and significant effect on the SDG Index. These findings show the complexity of the correlation among variables and the need for integrated policies that look upon the interaction between corruption and shadow economy in an effort to improve economic performance and achieve sustainable development in ASEAN developing countries.